A multiscale analysis of investments placement in the regions of the European part of Russia in the post-Soviet period - Nataliya Aleksandrovna Schitova; Liliya Igorevna Korneva (Наука. Инновации. Технологии)
The article is devoted to the complex geographical research of the peculiarities of placement and localization of investments in different territorial levels of the European part of Russia in the post-Soviet period. The research is based on the ideas of multiscale and territorial approaches in combination with the method of "keys",being relianced on geoinformation technologies. The main methodological setting consists in the sequential coupled analysis of data on the location of investments and the transformation of the territorial-sectoral structure of the economy at different territorial levels. The typology of Russian regions in terms of investment activity is conducted on the basis of comparative spatio-temporal analysis of economic parameters of key economic regions (Central, region Volga region and North-Caucasian regions) and such regions as(Kaluga and Smolensk regions, Republics of Ingushetia and Tatarstan, Stavropol Territory).That development of the investment process in the European part of Russia was phased in, accompanied by a little change in the centers and areas of investment. The article clarifies that main factors influencing the attracting of investments and their effect in different conditions establish some common features in the allocation of investments, in particular, their attraction to sustainable nodal elements of the territorial structure of the economy in the region and transit transport routes.